Reliability and risk issues in large scale safety-critical digital control systems - Seong, Poong-Hyun (Springer, 2017)
Reliability and Risk Issues in Large Scale Safety-critical Digital Control Systems provides some important coverage of reliability issues and their corresponding countermeasures in the field of large-scale digital control systems, from the hardware and software in digital systems to the human operators who supervise the overall process of large-scale systems. Unlike other books which examine theories and issues in individual fields, this book reviews important problems and countermeasures across the fields of hardware and system reliability, software reliability, verification and validation, digital systems, human factors engineering and human reliability analysis. Divided into four sections dealing with hardware and digital system reliability, software reliability, human reliability and human operators in integrated large scale digital systems operation, Reliability and Risk Issues in Large Scale Safety-critical Digital Control Systems offers insights from professional researchers in each specialized field in a diverse yet unified approach.